Disease Modifiers of Inherited SCN5A Channelopathy - Verkerk, Arie O.; Amin, Ahmad S.; Remme, Carol Ann (Frontiers in Cardiovascular Medicine, 2018)
To date, a large number of mutations in SCN5A, the gene encoding the pore-forming α-subunit of the primary cardiac Na+ channel (NaV1.5), have been found in patients presenting with a wide range of ECG abnormalities and cardiac syndromes. Although these mutations all affect the same NaV1.5 channel, the associated cardiac syndromes each display distinct phenotypical and biophysical characteristics. Variable disease expressivity has also been reported, where one particular mutation in SCN5A may lead to either one particular symptom, a range of various clinical signs, or no symptoms at all, even within one single family. Additionally, disease severity may vary considerably between patients carrying the same mutation. The exact reasons are unknown, but evidence is increasing that various cardiac and non-cardiac conditions can influence the expressivity and severity of inherited SCN5A channelopathies. In this review, we provide a summary of identified disease entities caused by SCN5A mutations, and give an overview of co-morbidities and other (non)-genetic factors which may modify SCN5A channelopathies. A comprehensive knowledge of these modulatory factors is not only essential for a complete understanding of the diverse clinical phenotypes associated with SCN5A mutations, but also for successful development of effective risk stratification and (alternative) treatment paradigms.